Customer satisfaction as a mediator between service quality and customer loyalty: a case study of Bank Central Asia - Cleming Tedjokusumo; Werner R. Murhadi (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
Purpose – This study aims to examine the effect of service quality on customer satisfaction and the impact of customer satisfaction on customer loyalty among banking service users in Indonesia. Design/methodology/approach – The population of this study consists of customers aged 18 years and above who use the mobile banking service provided by Bank Central Asia, one of the largest banking companies in Indonesia in terms of market capitalization. Purposive sampling was used to obtain a sample of 194 respondents who met the research criteria. Findings – The results of this study indicate that the reliability, customer service and support, and responsiveness variables have a significant positive influence on customer satisfaction, while the privacy and security variable was found to have no significant impact on customer satisfaction. Additionally, customer satisfaction was found to have a significant positive effect on customer loyalty. Research limitations/implications – The data for this study primarily came from East Java, Indonesia, highlighting the need for future research using longitudinal data to investigate the causal relationships between variables. Practical implications – The findings of this study can provide valuable insights into the influence of electronic service quality on customer loyalty in the Indonesian banking industry. It offers banks a deeper understanding of consumer behavior and the crucial satisfaction factors that drive long-term decision-making in banking services. Originality/value – This paper offers novelty by addressing the digitalization trend and competitive challenges faced by banking service providers in achieving customer satisfaction within the digital economic ecosystem. It specifically focuses on customers of Bank Central Asia, a leading banking company in Indonesia. The value of this paper lies in its insights for banking professionals, researchers, and policymakers in navigating the digital landscape and enhancing customer-centric digital banking services.